Taking advantage of the potential of mesenchymal stromal cells in liver regeneration: Cells and extracellular vesicles as therapeutic strategies - Fiore, Esteban Juan (2018)
Cell-based therapies for acute and chronic liver diseases are under continuous progress. Mesenchymal stem/stromal cells (MSCs) are multipotent cells able to migrate selectively to damaged tissue and contribute to its healing and regeneration. The MSC pro-regenerative effect occurs due to their immunomodulatory capacity and their ability to produce factors that promote cell protection and survival. Likewise, it has been observed that part of their paracrine effect is mediated by MSC-derived extracellular vesicles (EVs). EVs contain proteins, lipids and nucleic acids (DNA, mRNA, miRNA, lncRNA) from the cell of origin, allowing for intercellular communication. Recently, different studies have demonstrated that MSC-derived EVs could reproduce, at least in part, the biological effects obtained by MSC-based therapies. Moreover, due to EVs’ stability for long periods of time and easy isolation methods they have become a therapeutic option to MSCs treatments. This review summarizes the latest results achieved in clinical trials using MSCs as cell therapy for liver regeneration, the role of EVs in liver physiopathology and the potential of MSC-derived EVs as intercellular mediators and therapeutic tools in liver diseases.